Age‐dependent effect between MARCO and TLR4 on PMMA particle phagocytosis by macrophages. Issue 8 (21st June 2019) - Yamada, Chiaki; Beron‐Pelusso, Camila; Algazzaz, Neira; Heidari, Alireza; Luz, Diogo; Rawas‐Qalaji, Mutasem; Toderas, Ion; Mascarenhas, Ana Karina; Kawai, Toshihisa; Movila, Alexandru
Abstract: Progressive generation of total joint implant‐derived wear particles is one of the major risk factors in development of peri‐prosthetic osteolysis especially in the aging society. It is commonly accepted that macrophages predominantly drive the inflammatory response to wear debris particles. Among various surface receptors that activate the macrophages to phagocytize particles, it is believed that the Toll‐like receptor 4 (TLR4) and the scavenger macrophage receptor with collagenous structure (MARCO) play key roles in recognition of wear debris particles. However, a strong body of evidence indicates an age‐dependent diminished function of human TLRs. Thus, we hypothesized that the MARCO receptor may be more engaged than TLRs in the phagocytosis of wear debris particles which in turn up‐regulate production of pro‐inflammatory cytokines from aged macrophages. We demonstrated that peritoneal macrophages isolated from aged mice show elevated expression of MARCO receptor compared to that from young mice. In contrast the expression of TLR4 was significantly decreased on the surface of aged macrophages. Furthermore, using anti‐MARCO and anti‐TLR4 neutralizing mAbs, we demonstrated the age‐dependent pathogenic role of MARCO, but not TLR4, receptor in promoting poly‐methyl methacrylate (PMMA) bone cement particles phagocytosis by macrophages leading to the release of pro‐inflammatory cytokines migration inhibitory factor and tumour necrosis factor in vitro. These data also suggest that the approach to neutralize MARCO may lead to the development of therapeutic regimen for the prevention of particle‐induced osteolysis in aged patients.